Pharmacological and toxicological characteristics of baicalin in preventing spontaneous abortion and recurrent pregnancy loss: A multi-level critical review - Linwen Deng; Yue Jin; Xiaoyan Zheng; Yi Yang; Yong Feng; Hang Zhou; Qian Zeng (Heliyon)
Relevance: Spontaneous abortion (SAB) and recurrent pregnancy loss (RPL) occur alone or concurrently with increasing incidences recently. Scutellaria baicalensis Georgi (SBG) has been used to prevent pregnancy loss for thousands of years, which is recognized as a “pregnancy-stabilizing herb” in ancient China. Baicalin (BA) and its metabolite baicalein (BE) are the main bioactive flavonoids in the root of SBG. Methods: In this study, we focused particularly on the metabolism, toxicology, and pharmacological effects of BA at the maternal-fetal interface based on the biological process prediction by network pharmacology. Focused on the systematic review of BA's regulatory mechanisms of immune homeostasis, cell proliferation and invasion, programmed cell death, inflammatory microenvironment, angiogenesis, oxidative stress and vascular remodeling at the maternal-fetal interface, it was found that BA exerts its biological effects to treat SAB and RPL through multiple perspectives and targets. We also critically elucidated the limitations of using BA from a clinical perspective. Results: We explored the bioavailability, targeting and efficacy of BA from a new perspective (optimization of the BA delivery system, organoid studies based on BA, potential effects of BA on uterine flora and bioactive components). Finally, we propose a multimodal stereo sequencing study of biologically active components based on pathological dynamics incorporating single-cell RNA sequencing, spatially resolved transcriptomics, and single-cell multimodal omics to delve deeper into the fetal-preserving mechanism of BA and to promote the application of BA in clinical practice.